Netnografi Pesan Moral Dalam Vlog Atap Negeri Fiersa Besari - Agustian, Dimas Joni; SM, Anis Endang; Octaviani, Vethy Octaviani (UNIVED PRESS, Universitas Dehasen Bengkulu, 2024)
The rapid development of information technology has encouraged the presence of social media which has influenced changes in people's lifestyles and communication patterns. One product of this technological development is YouTube. This research aims to find out the moral message in the Atap Negeri vlog on Fiersa Besari's Youtube in the video entitled